Public Administrative Efficiency within the Framework of the Neo-Weberian State an Analysis of the “One Application, Five Outcomes” Innovation by the Luwuk Branch of BPJS Kesehatan - Fahmi, Uzdatun Nabilah; Wardiyanto, Bintoro (Journal Research of Social Science, Economics, and Management, 2026)
This research aims to analyze the public service innovation "Satu Lahir Lima Terbit" (SABIT) initiated by the BPJS Kesehatan Luwuk Branch Office through the perspective of the Neo-Weberian State (NWS) theory, and to describe the mechanism of implementation of the innovation and analyze its conformity with the principles of NWS. This study uses a SLR approach with a qualitative descriptive method to analyze SABIT's innovation that integrates a digital birth reporting system to fulfill the administrative rights of newborns by enabling health facilities, the Population and Civil Registration Office, and BPJS Kesehatan to issue five official documents simultaneously in the period 2022–2025, which integrates a digital birth reporting system to fulfill the administrative rights of newborns by enabling healthcare facilities, the Civil Registry and Population Administration Office and BPJS Kesehatan to simultaneously issue five official documents. The method employed is descriptive qualitative through a systematic literature review. It explores how SABIT reconciles the hierarchical structures of traditional bureaucracy with the flexibility of a modern managerial system. The findings indicate that SABIT has successfully improved bureaucratic efficiency and data accuracy, for instance, 90% of birth certificates are issued within 24 hours, and an average of 60 newborns are served per day. This innovation also strengthens state legitimacy in guaranteeing citizens' constitutional rights from birth. The NWS model offers an inter-agency integration approach, focused on outcomes and the use of information technology for public services, as it can balance legal certainty with inclusive service innovation